Video-assisted thoracoscopic surgery (VATS) right upper lobectomy for non-small-cell lung cancer with an azygos lobe - Samancilar, Ozgur; Akcam, Tevfik Ilker; Kaya, Seyda Ors; Sevinc, Serpil; Akcay, Onur; Ceylan, Kenan (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2016)
Although it is not a pathologically significant entity, cases of azygos lobe (AL) are interesting due to the difficulty of performing video-assisted thoracoscopic surgery (VATS) procedures in the affected patients and the presence of a congenital malformation. Currently, videothoracoscopic surgery has advanced to such a level that most thoracic procedures can be performed with video assistance. However, some technical difficulties may arise in cases with anatomical anomalies such as AL. This report presents the case of a patient with an azygos lobe who underwent videothoracoscopic lung resection due to the presence of non-small-cell lung carcinoma in the upper lobe of the right lung.